Do foot & ankle assessments assist the explanation of 1 year knee arthroplasty outcomes?. Issue 6 (June 2017) - Gates, L.S.; Bowen, C.J.; Sanchez-Santos, M.T.; Delmestri, A.; Arden, N.K.
Summary: Objective: Whilst a number of risk factors for poor patient reported outcome measures (PROMs) following knee arthroplasty (KA) have been identified, unexplained variability still remains. The role of pre-operative foot and ankle status on such outcomes has not been investigated. The aim of this study was therefore to determine the association of clinical foot and ankle assessments with patient reported outcomes 1 year following KA. Design: One hundred and fifteen participants from the Clinical Outcomes in Arthroplasty Study (COASt), underwent detailed foot and ankle assessments at baseline, prior to KA (2012–2014) and were followed up for self-reported outcomes 1 year after surgery. Results: Thirty nine percent of subjects reported foot pain at baseline. Mean pre-operative Oxford Knee Score (OKS; 0 [worst] to 48 [best outcome]) was 21 and post-operative OKS score was 38. In fully adjusted analysis pre-operative foot pain was significantly associated with 1 year outcome (risk ratio [RR] 0.78 95% confidence interval [95% CI] 0.62, 0.98). No significant association was observed between ankle dorsiflexion or foot posture and outcome. Conclusions: Patients with pre-operative foot pain are more likely to have poorer clinically important outcomes 1 year following KA than patients without foot pain. Static ankle dorsiflexion and foot posture do not further explain post-operative KA outcomes. Consideration should also be given to address pre-operative foot pain when attempting to achieve a good clinical outcome for KA.